Entrepreneurial entry: which institutions matter? - Ruta Aidis; Saul Estrin; Tomasz Mickiewicz (Institute for the Study of Labor (IZA), 2009)
In this paper we explore the relationship between the individual decision to become an entrepreneur and the institutional context. We pinpoint the critical roles of property rights and the size of the state sector for entrepreneurial activity and test the relationships empirically by combining country-level institutional indicators for 44 countries with working age population survey data taken from the Global Enterprise Monitor. A methodological contribution is the use of factor analysis to reduce the statistical problems with the array of highly collinear institutional indicators. We find that the key institutional features that enhance entrepreneurial activity are indeed the rule of law and limits to the state sector. However, these results are sensitive to the level of development.
urn:nbn:de:101:1-20090513209
Keywords: L26; P14; P51; P37; 330; Entrepreneurship; property rights; access to finance; Unternehmer; Unternehmensgründung; Institutionelle Infrastruktur; Eigentumsrecht; Staatsquote; Welt